Consumers’ preferences to web cookie banners regarding data privacy in the Czech Republic - Phan, Duyen Nu Hanh; Hron, Michal; Mareš, Jan, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis studies customer perception and behavior in response to cookie banners on websites, which gives insight into users’ attitudes and reactions toward data privacy on online tracking businesses. The paper consists of theoretical and practical parts. The first half is for literature reviews, aiming to provide a better context for data and internet cookies in general. In this section, a mixed methodology of a qualitative content analysis and quantitative surveys applied to the thesis is also elaborated. While the qualitative content analysis exposes the details of cookie banners’ designs, based on which an experimental comparison is developed, two quantitative surveys are constructed and administered accordingly. Thanks to the participation of 62 individuals and the implementation of various statistical tests, the empirical analyses of the surveys show that users might not be particularly sensitive to the exposure of cookie banners’ visual elements. Instead, their decision to consent is more influenced by what they know or do not know about cookies and in certain cases, what they feel about the website itself. Such discoveries might help businesses better understand consumers’ references and adjust accordingly in order to enhance user engagement as well as user consent.
Vedoucí práce: Michal Hron
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses